Locality Effect of Coral-Associated Bacterial Community in the Kuroshio Current From Taiwan to Japan - Yang, Shan-Hua; Tseng, Ching-Hung; Lo, Hsueh-Ping; Chiang, Pei-Wen; Chen, Hsing-Ju; Shiu, Jia-Ho; Lai, Hung-Chun; Tandon, Kshitij; Isomura, Naoko; Mezaki, Takuma; Yamamoto, Hiromi; Tang, Sen-Lin (Frontiers in Ecology and Evolution, 2020)
The Kuroshio Current (KC) is one of the fastest water currents in the world, running through the western boundary of the North Pacific Ocean. The KC strongly influences the regional hydroclimate by creating temperature, salinity, and pH gradients from tropical to subtropical and temperate zones, including regions with rich coral reef habitats. Microbial community composition of corals is influenced by various environmental factors, including salinity, pH, and geographical location. However, to date, it is unclear how coral-associated microbial communities would respond to the same water current running through different locations with a time lag. Therefore, we hypothesized that the locations subjected to the KC at higher latitudes experience similar but delayed environmental conditions compared to those at lower latitudes, and thus the coral communities of both will respond similarly, but at different times. In this yearlong study, we compared the bacterial communities of Acropora muricata at Taiwan, Okinawa, and Kochi subjected to the KC. We found that site-specific conditions and site latitude may have stronger effects on bacterial composition and dynamics than a water current. Consequently, we suggest that latitude largely determines the temperature tolerance range of coral microbiota. Additionally, among the dominant coral associated bacteria, Endozoicomonas from A. muricata and Stylophora pistillata forms distinct phylogroups, while Acinetobacter is more likely a host generalist.